Isolation and Establishment of a Highly Proliferative, Cancer Stem Cell-Like, and Naturally Immortalized Triple-Negative Breast Cancer Cell Line, KAIMRC2 - Rizwan Ali; Hajar Al Zahrani; Tlili Barhoumi; Alshaimaa Alhallaj; Abdullah Mashhour; Musaad A. Alshammari; Yasser A. Alshawakir; Omar Baz; Abdullah H. Alanazi; Abdul Latif Khan; Hassan Al Nikhli; Mohammed A. Al Balwi; et al. (Cells, 2021)
In vitro studies of a disease are key to any in vivo investigation in understanding the disease and developing new therapy regimens. Immortalized cancer cell lines are the best and easiest model for studying cancer in vitro. Here, we report the establishment of a naturally immortalized highly tumorigenic and triple-negative breast cancer cell line, KAIMRC2. This cell line is derived from a Saudi Arabian female breast cancer patient with invasive ductal carcinoma. Immunocytochemistry showed a significant ratio of the KAIMRC2 cells’ expressing key breast epithelial and cancer stem cells (CSCs) markers, including CD47, CD133, CD49f, CD44, and ALDH-1A1. Gene and protein expression analysis showed overexpression of ABC transporter and AKT-PI3Kinase as well as JAK/STAT signaling pathways. In contrast, the absence of the tumor suppressor genes p53 and p73 may explain their high proliferative index. The mice model also confirmed the tumorigenic potential of the KAIMRC2 cell line, and drug tolerance studies revealed few very potent candidates. Our results confirmed an aggressive phenotype with metastatic potential and cancer stem cell-like characteristics of the KAIMR2 cell line. Furthermore, we have also presented potent small molecule inhibitors, especially Ryuvidine, that can be further developed, alone or in synergy with other potent inhibitors, to target multiple cancer-related pathways.